2016
DOI: 10.1002/asia.201601400
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in BODIPY in Live Cell Imaging

Abstract: Small-molecule organoselenium-based fluorescent probes possess great capacity in understanding biological processes through the detection of various analytes such as reactive oxygen/nitrogen species (ROS/RNS), biothiols (cysteine, homocysteine and glutathione), lipid droplets, etc. Herein, we present how substituents on the BODIPY system play a significant part in the detection of biologically important analytes for in vitro conditions and live cell imaging studies. The fluorescence of the probe was quenched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 94 publications
2
30
0
Order By: Relevance
“…Confocal fluorescence microscopy imaging demonstrated that the probe could be utilized to evaluate the important roles of HClO/GSH in biological systems. By employing the oxidation and reduction of selenium/tellurium, Churchill and co‐workers described three probes ( 88 , 89 , and 90 ) for monitoring of the ROS/biothiols redox cycle (Figure ) …”
Section: Bodipy‐based Probes For Biothiolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal fluorescence microscopy imaging demonstrated that the probe could be utilized to evaluate the important roles of HClO/GSH in biological systems. By employing the oxidation and reduction of selenium/tellurium, Churchill and co‐workers described three probes ( 88 , 89 , and 90 ) for monitoring of the ROS/biothiols redox cycle (Figure ) …”
Section: Bodipy‐based Probes For Biothiolsmentioning
confidence: 99%
“…[115,116] In this section, we only highlight BODIPYbased reversible probesfor ROS/biothiols. [117][118][119][120][121][122][123] By exploitingt he oxidation and reduction of selenium, Han's group developed probe 85 by installation of ad iphenyl selenium moiety via the para position into the meso of BODIP for the detection of the HClO/H 2 Sr edox cycle (Scheme 10). [117] When the probe was oxidized by HClO, ab right green fluorescence (510 nm) increment was observed.…”
Section: Reversible Probes For Ros/biothiolsmentioning
confidence: 99%
See 1 more Smart Citation
“…We show now that BODIPYs( Scheme1)a re able to generate the T 1 state based on ad ifferent mechanism.B ODIPY and its derivatives are well-known highlyf luorescent materials for various applications, [13][14][15][16][17] but these dyes lack the ability to produce the T 1 state upon photo excitation. [12,18,19] Unsubstituted BODIPY,f or example, shows fluorescencee fficiency near unity (0.97 AE 0.03) and al ong fluorescence lifetime of 6.89 ns in methanol, [20] which leaves it little space to form the T 1 state.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, the Churchill group incorporated the BODIPY system with a single mesityl moiety (C 6 Me 3 H 3 ) at the so‐called meso position of the fluorophore; it turns out to play a significant part in the detection of ROS for in vitro and live cell imaging studies (Scheme ) . The addition of 2‐chloro and 6‐phenyl selenium groups within the BODIPY periphery served to quench the fluorescence due to a photoinduced electron transfer (PET) effect (Figure ); the probe shows high selectivity with NaOCl among other ROS/RNS; a maximum fluorescence intensity is achieved within 1 min and involved a low detection limit (19.6 n m ) and a 110‐fold fluorescence enhancement, compared to the signals generated upon the addition of other ROS/RNS.…”
Section: Introductionmentioning
confidence: 99%